Office blood pressure measurements with oscillometric devices in adolescents: a comparison with home blood pressure - Thiago Veiga Jardim; Thomas A. Gaziano; Flávia Miquetichuc Nascente; Carolina de Souza Carneiro; Polyana Morais; Vanessa Roriz; Karla Lorena Mendonça; Thaís Inácio Rolim Póvoa; Weimar Kunz Sebba Barroso; Ana Luiza Lima Sousa; Paulo César Veiga Jardim (Blood Pressure, 2017)
Purpose: Compare multiple in office BP measurements in adolescents using an oscillometric device with out-of-office blood pressure measurements (home blood pressure monitoring – HBPM). Materials and methods: Office measurements were performed with validated semi-automatic devices twice (3 minutes interval) in two different moments (1 week apart), with a total of four readings. These BP readings were named R1, R2, R3 and R4 (following the sequence they were performed), FDM (mean of two readings on first day) and SDM (mean of two readings on second day) and SRM (R2–R4 means). The HBPM protocol included two day-time and two evening-time measurements over 6 days. Results: A total of 1024 students between 12 and 17 years were included (mean age 14.68 years; 52.4% females). The mean systolic blood pressure (SBP) values of R2, SDM and SRM were similar to HBPM values. Regarding diastolic blood pressure (DBP) HBPM value was different than R4. High SBP and DBP correlation coefficients with HBPM values were found for R2, SDM and SRM values. Conclusion: The second office BP measurement performed with an oscilometric device in adolescents was comparable to HBPM values, suggesting that two office readings might be suitable to rule out hypertension in this age group.